Environmental Life Cycle Assessment of Linoleum. - Gorree, Marieke (The International Journal of Life Cycle Assessment)
Linoleum is a floor covering consisting mainly of linseed oil, other vegetable oils, wood flour and limestone on a carrier of jute. Forbo-Krommenie B. V. commissioned the Centre of Environmental Science (CML) to carry out an Environmental Life Cycle Assessment for linoleum floors. The goal of this study was to assess the environmental performance of linoleum floors, indicating possible options for improvement and assessing the sensitivity of the results to methodological choices. The functional unit was defined as 2000 m2 linoleum produced in 1998, used in an office or public building over a period of 20 years. The method followed in this study is based on a nearly final draft version of the LCA guide published by CML in corporation with many others, which is an update of the guide on LCA of 1992. From the contribution analysis, the main contributing processes became clear. In addition, the sensitivity analysis by scenarios showed that the type of maintenance during use and the pigments used can have a large influence on the results. Major data gaps of the study were capital goods and unknown chemicals. Sensitivity analysis also showed that these gaps can lead to an underestimation. Based on this study, some options to improve the environmental performance of linoleum were formulated and advice for further LCA studies on linoleum was given.